PHYTOINDICATION OF CLIMATIC REGIMES OF FOREST ECOSYSTEMS ECOTOPES FOR CENTRAL RUSSIAN UPLAND STEPPE AND FOREST FORESTRY DISTRICT OF UKRAINE - Bondaruk, M. A.; Tselishchev, A. G. (Forestry and Forest Melioration, 2018)
Introduction Issues of phytoindication and phytomonitoring of major ecological factors for large-scale regional (zonal) investigations are analyzed. Materials and methods Subjects of research are the first level monitoring plots (114 plots), located in Kharkiv and Sumy regions within Central Russian Upland Steppe and Forest forestry district of Ukraine. Method of phytoindication of major factors on unified ecological scales for Ukrainian flora species (Ya.P. Didukh, 2011) was used for indication of ecoregimes in forest ecosystems ecotopes, definition of such microclimatic indicators of ecotopes as thermoregime, contrast regime, cryoregime and features of their changes according to the types of forest growth conditions. A concept of “eco-background” - the background factors of forests (a range of values within the limits of standard deviations) - interpreted as a reference point, in relation to which the direction and intensity of edaphic and climatic processes are measured in the forest ecotopes of specific region, and within the region - in the ecotopes of the coniferous, mixed and broad-leaved forests, is proposed for the comparative monitoring of fluctuations and dynamics of the ecological regimes in relation to typical and zonally-provided values in the forest ecotopes of the region. Results. Discussion The major climatic factors which predetermine the differentiation of forest ecotopes on the level of Central Russian Upland Steppe and Forest forestry district are radiation balance, continental climate and cryo-climate (ecological amplitude is from 11,4 to 15,4 % in relation to the scale of every factor). The differentiation of indexes for basic climatic factors in forest ecotopes at the level of forestry district is caused by the zonal features of the ecological regimes forming in the different types of forest growth conditions and by the specific structure of the coniferous, mixed and leafy forest communities. There were investigated the climatic eco-background, as a component of the eco-background of district’s forests and within the district - separate climatic eco-backgrounds of coniferous, mixed and broad-leaved forests. Forest ecotopes in Central Russian Upland Steppe and Forest forestry district are characterized by the following variability of microclimatic indices (within standard deviation): thermo-background – approximate to Sub-mesotherms (Tm = 41 ? 44 kcal/сm2/year, or 1717-1842 МJ m2/year), contrast-background corresponds to the regime intermediate between Hemi-oceanic and Hemi-continental (Kn = 121 ? 130%), cryo-background – intermediate between Sub-cryophytes with moderate winters and Hemi-cryophytes with soft winters (Cr = -9,0 ? -6,0°С). Conclusions The expounded methodical approaches of phytoindication and examples of their application expose the perspective of this scientific direction for the regional (zonal) ecological monitoring of ecological regimes in forest ecotopes. Minimum, average and maximal values of the ecological regimes for types of forest growth conditions, for forest communities (coniferous, mixed, broad-leaved) and for the district in whole, amplitudes of the ecoregimes of forest ecosystems’ ecotopes relative to the scales of ecological factors, eco-background of district forests and separate eco-backgrounds of the coniferous, mixed and broad-leaved forests are acknowledged as the indices of regularities of change of certain ecological factors, and differentiation of forest ecosystems’ ecotopes.